4(x-5)+4(x-5)+3(x+6)+3(x+6)=

Simple and best practice solution for 4(x-5)+4(x-5)+3(x+6)+3(x+6)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x-5)+4(x-5)+3(x+6)+3(x+6)= equation:


Simplifying
4(x + -5) + 4(x + -5) + 3(x + 6) + 3(x + 6) = 0

Reorder the terms:
4(-5 + x) + 4(x + -5) + 3(x + 6) + 3(x + 6) = 0
(-5 * 4 + x * 4) + 4(x + -5) + 3(x + 6) + 3(x + 6) = 0
(-20 + 4x) + 4(x + -5) + 3(x + 6) + 3(x + 6) = 0

Reorder the terms:
-20 + 4x + 4(-5 + x) + 3(x + 6) + 3(x + 6) = 0
-20 + 4x + (-5 * 4 + x * 4) + 3(x + 6) + 3(x + 6) = 0
-20 + 4x + (-20 + 4x) + 3(x + 6) + 3(x + 6) = 0

Reorder the terms:
-20 + 4x + -20 + 4x + 3(6 + x) + 3(x + 6) = 0
-20 + 4x + -20 + 4x + (6 * 3 + x * 3) + 3(x + 6) = 0
-20 + 4x + -20 + 4x + (18 + 3x) + 3(x + 6) = 0

Reorder the terms:
-20 + 4x + -20 + 4x + 18 + 3x + 3(6 + x) = 0
-20 + 4x + -20 + 4x + 18 + 3x + (6 * 3 + x * 3) = 0
-20 + 4x + -20 + 4x + 18 + 3x + (18 + 3x) = 0

Reorder the terms:
-20 + -20 + 18 + 18 + 4x + 4x + 3x + 3x = 0

Combine like terms: -20 + -20 = -40
-40 + 18 + 18 + 4x + 4x + 3x + 3x = 0

Combine like terms: -40 + 18 = -22
-22 + 18 + 4x + 4x + 3x + 3x = 0

Combine like terms: -22 + 18 = -4
-4 + 4x + 4x + 3x + 3x = 0

Combine like terms: 4x + 4x = 8x
-4 + 8x + 3x + 3x = 0

Combine like terms: 8x + 3x = 11x
-4 + 11x + 3x = 0

Combine like terms: 11x + 3x = 14x
-4 + 14x = 0

Solving
-4 + 14x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4' to each side of the equation.
-4 + 4 + 14x = 0 + 4

Combine like terms: -4 + 4 = 0
0 + 14x = 0 + 4
14x = 0 + 4

Combine like terms: 0 + 4 = 4
14x = 4

Divide each side by '14'.
x = 0.2857142857

Simplifying
x = 0.2857142857

See similar equations:

| 8y+9y-y-4+1y-4y=36 | | 5n-7=5(n+2)+3 | | A=pt-3p | | 1/2-3=9 | | 9(8-12w)= | | 5(x-3)=-(15-5x) | | -68+4x+3x=114 | | 5x/2=-3x+11 | | 5p-2(4-2p)=19 | | Y=-2+-0.6666666667x | | -3/7w=9 | | 2x-(2-x)=13 | | x=(2m-4)/(1+n) | | 125^-2/3 | | 7x^2+40x+25=0 | | 9x-8x-10=13 | | 9.05=8.2 | | 3[8y+2]=10y+2[7y+3] | | 5/12=6/x | | 9+9-1-2+5m-1-4m=32 | | t*5=54 | | 3x-(5+2x)= | | x+4x-73=72 | | 10/3x2/5 | | 5x+16=2X | | 6x/3-18 | | 3/10(220) | | 2-3t+6+4t-12=9t | | 3c+8=5c+11 | | 2n+8=17 | | 555,555,555+124,135,352,246= | | 3Q-1+10-4+1-1-2=20 |

Equations solver categories